Методи збереження та використання об’єктів природно-заповідного фонду у структурі міст - Тупісь, Степан Павлович (Національний університет "Львівська політехніка", 2019)
У дисертації наведене теоретичне узагальнення в питаннях збереження, використання та планування природоохоронних об’єктів. Запропоноване вирішення наукової проблеми відсутності принципів охорони цінних природних ресурсів міста. На основі визначених особливостей міських природно-заповідних об’єктів та чинників впливу на них сформульовано принципи збереження та використання природоохоронних об’єктів природного і штучного походження. Розроблено методичні рекомендації щодо планування об’єктів природно-заповідного фонду в містах та встановлено види і засоби їх містобудівного регулювання. В диссертации приведено теоретическое обобщение в вопросах сохранения, использования и планирования природоохранных объектов. Предложенное решение научной проблемы отсутствия принципов охраны наиболее ценных природных ресурсов города. На основе определенных особенностей городских природно-заповедных объектов и факторов влияния на них сформулированы принципы сохранения и использования природоохранных объектов природного и искусственного происхождения. Разработаны методические рекомендации по планированию объектов природно-заповедного фонда в городах и установлены виды и средства их градостроительного. The thesis presents theoretical generalization of the issues of preservation, use, and planning of protected sites. A solution to the scientific problem of architectural regulation of nature reserve facilities in the city structure for the purpose of their preservation was suggested. It has been determined that processes that take place in adjacent territories have the greatest influence on the state of nature reserve facilities in the urbanized environment: - high urban density leads to critical operational pressure on protected areas; - industrial facilities and economic activity lead to pollution of surface and ground waters; - at the sites where administrative and biological boundaries do not coincide, natural elements found outside nature reserve facilities deteriorate, thus disrupting biological processes of the entire nature reserve facility. As for the preservation of protected areas, the main theoretical basis of the work is the need to form continuous natural territorial networks, which are more resistant to the impact of urbanization processes than discrete (discontinuous) ones. Natural elements which have been newly discovered within wildlife corridors may claim to be included in the lists of nature reserve facilities. Justified emergence of new nature reserve facilities and their protected areas will make the system of protected sites more sustainable. The following recommendations were formulated for the preservation and use of nature reserve facilities: - zoning of nature reserve facilities by permissible uses based on natural zoning; - restriction on the use of territories adjacent to nature reserve facilities within the protected zone. For this purpose, the following shall be established: limited economic activity zone - 50 meters - territory allocated for the preservation of the closest natural surroundings of the nature reserve facility, and development control zone - 200 m - distance necessary to counteract harmful effects of the urbanized environment. A "protected landscape zone" shall be formed outside the protected area, which plays a stabilizing role, preserving and restoring natural and landscape qualities of the territories with which a nature reserve facility has an environmentally sound connection. The size of the zone is not regulated, but it is determined on the basis of connections of a nature reserve facility in the landscape system of a city. - introduction of environmental regulations into Zoning documentation by updating the list of areas of landscape and ecological importance for the purpose of determining natural areas with the highest level of preservation of flora and hydrological and biological processes of all types. As a means of implementing the developed methodological regulations of the preserving and using of nature reserve facilities of all types it is recommended to certificate nature reserve facilities.
Методы сохранения и использования объектов природно-заповедного фонда в структуре городов
Methods of preserving and using of nature reserve facilities in the structure of cities
Keywords: природно-заповідний фонд; екологічна мережа міста; ландшафт; охоронна зона; природно-заповедный фонд; экологическая сеть города; ландшафт; охранная зона; nature reserve; ecological network of a city; landscape; protected area; restricted area; 711.4+712.23:502.4